Meaning of becoming mother and son/daughter through massage - Francisca Márquez Doren; Camila Lucchini Raies; Soledad Rivera Martínez (SciELO, 2014)
Objective: Revealing the experience of mothers when massaging their children to know the phenomenon in the context of a mother-child healthy development. Method: This is a qualitative study with a phenomenological approach carried out with 11 women who massaged their children and answered the guiding question: What did the experience of massaging your child mean to you? Results: The experience of massaging their children meant the development of their being a mother and of being a son/daughter, in addition to developing the attachment relationship between them. The massage can operationalize this integrality, become a tool of communication, stimulation and promotion of secure attachment, by promoting the loving interaction between mother and child. Conclusion: This practice should be considered as an option in the programs that promote the comprehensive health of the mother and child.